2005
DOI: 10.1021/es051703p
|View full text |Cite
|
Sign up to set email alerts
|

NMR Investigation of the Behavior of an Organothiophosphate Pesticide, Chlorpyrifos, Sorbed on Soil Components

Abstract: Phosphorus-31 nuclear magnetic resonance (31P NMR) was used to follow the decomposition of chlorpyrifos (an organothiophosphate pesticide) adsorbed on soil, humic acid, partially hydrated kaolin clay, and partially hydrated montmorillonite clay at high concentration (typically 2-10 wt %). Solid-state 31P NMR (using magic-angle spinning and cross polarization or direct polarization) and liquid-solution 31P NMR of DMSO and acetone extracts indicate that chlorpyrifos is initially physisorbed, appearing by solid-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The distinctive high K OC found for CME soil could be attributed to its high clay content and to the presence of montmorillonite. This compound is sorbed on montmorillonite, kaolinite, and gibbsite (Seger and Maciel 2005;Van Emmerik et al 2007). …”
Section: Adsorptionmentioning
confidence: 99%
“…The distinctive high K OC found for CME soil could be attributed to its high clay content and to the presence of montmorillonite. This compound is sorbed on montmorillonite, kaolinite, and gibbsite (Seger and Maciel 2005;Van Emmerik et al 2007). …”
Section: Adsorptionmentioning
confidence: 99%
“…Though SiO 2 is often used as a background particle for its lack of toxicity to bacteria [1], the investigation of Adams et al [2] suggested that nano-SiO 2 could inhibit bacterial growth. As a kind of naturally abundant mineral, kaolinite has been widely studied as adsorbent for removal of metal ions and organic pollutants from water [3][4][5][6]. To our knowledge, little investigation has been made on the sorption of organic pollutant by nano-SiO 2 and kaolinite coated with HA.…”
Section: Introductionmentioning
confidence: 99%
“…Seger and Maciel have presented a number of studies [127][128][129] about the degradation pathways of OP pesticides sorbed on soil and clay. The interesting aspect in these studies from the point of NMR was the application of solid-state 31 P MAS NMR in the direct analysis of soil and clay samples.…”
Section: Degradation In Environmentmentioning
confidence: 99%